2008
DOI: 10.1177/1753425908095958
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Profiling structural elements of short-chain lipopolysaccharide of non-typeable Haemophilus influenzae

Abstract: Lipopolysaccharide (LPS) is a major virulence determinant of the human bacterial pathogen Haemophilus influenzae. A characteristic feature of H. influenzae LPS is the extensive intra- and inter-strain heterogeneity of glycoform structure which is key to the role of the molecule in both commensal and disease-causing behaviour of the bacterium. The chemical composition of non-typeable Haemophilus influenzae (NTHi) LPS is highly diverse. It contains a number of different monosaccharides (Neu5Ac, L-glycero-D-manno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 73 publications
(177 reference statements)
0
9
0
Order By: Relevance
“…It is also found in core oligosaccharides from other Gram-negative bacteria, such as Haemophilus influenzae I-69 (40) and in non-typeable H. influenzae, where this position of Kdo carries a pyrophosphoethanolamine residue (41). Additionally, such phosphorylation has been identified in the inner core oligosaccharide of Bordetella pertussis (42) and Vibrio cholerae (43).…”
Section: Discussionmentioning
confidence: 96%
“…It is also found in core oligosaccharides from other Gram-negative bacteria, such as Haemophilus influenzae I-69 (40) and in non-typeable H. influenzae, where this position of Kdo carries a pyrophosphoethanolamine residue (41). Additionally, such phosphorylation has been identified in the inner core oligosaccharide of Bordetella pertussis (42) and Vibrio cholerae (43).…”
Section: Discussionmentioning
confidence: 96%
“…However, some Gram-negative bacteria are reported to contain less potent atypical LPS composed of lipid A with shorter or fewer acyl chains [39][41]. LPS derived from Haemophillus influenzae and Moraxella catarrhalis has been reported to contain hexa- and hepta-acylated lipid A, respectively [42], [43]. No studies have been reported on LPS of the Prevotella or Veillonella species included in our study; yet LPS from other species within these genera have been analyzed.…”
Section: Discussionmentioning
confidence: 82%
“…Whereas incorporation of a galactose on HepIII is considered to be a terminal moiety, glucose on HepIII can be substituted with galactose depending on lic2A gene activity (19), which is controlled by phase variation, a mechanism that switches translation of genes on or off (39). Phase-variable on-off translation of genes is a stochastic process dependent on slipped-strand mispairing of tandem repeats present in the gene, which occurs with a high frequency (10 −2 to 10 −3 times per generation) and leads to switching the coding region in or out of frame.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, variation and modifications in its lipooligosaccharide (LOS) composition have been shown to prevent complement activation (1518). The LOS structure of NTHi consists of three parts: (i) lipid A, (ii) an inner core comprised of a single 3-deoxy- d -manno-octulosonic acid (Kdo) linked to three conserved heptoses (Hep), and (iii) an outer core containing variable oligosaccharide extensions (19). Specific LOS structures have been shown to prevent binding of antibody and complement factor C4b, which increases their resistance to complement-mediated lysis (15, 16).…”
Section: Introductionmentioning
confidence: 99%